Structure-based insights into evolution of rhodopsins - Dmitrii Zabelskii (Nature Portfolio, 2021)
Zabelskii et al. present a structural and functional analysis of the lightdriven proton pump LR (Mac) from the fungus Leptosphaeria maculans. Their findings indicate that the archaeal ancestry of eukaryotic type 1 rhodopsins, and that the archaeal host of the proto-mitochondrial endosymbiont was capable of light-driven proton pumping.